Exploring the use of ARS-keepad Technology in English Vocabulary Development - Giridharan, Beena (AWEJ, 2013)
The lexical approach towards second language (L2) teaching focuses on developing learners’ proficiency with lexis, or words and word combinations. Language teachers and researchers are cognizant of the significant role of vocabulary in different pedagogical tasks and of the fact that mastery of vocabulary is an essential component of L2 learning (Mohseni-Far, 2008). An important aspect of L2 vocabulary learning is the capacity to comprehend and produce lexical phrases. This explorative study investigated the role of (Automated Response System) ARS-keepad technology as a pedagogical tool in the second language classroom for L2 vocabulary recognition tasks, and examined whether the technology could be used to utilize a higher level of interaction in the classroom and permit vocabulary comprehension to be assessed in real-time. Studies by cognitive scientist, Pinker (2000) assert that principles of language acquisition can be compared to a branch of theoretical computer science called Learnability Theory, which acknowledges the role of environment in language learning. This premise posits that an interactive instructional environment could play an important role in language learning including vocabulary development. A social learning theory such as the Constructivist theory is also explored in the study to explore whether ARS-keepad technology can promote a higher level of interaction among learners.Initial results from the study illustrate that the knowledge gains, through the use of ARS-keepad technology came firstly from the almost instantaneous feedback from learners to the instructor that facilitated development of relevant vocabulary learning tasks. It further assisted measurement of comprehension through well-designed questions, and by getting each learner to respond. The use of emerging technologies like ARS- keepad in the classroom allows for veering away from traditional teaching paths and learning practices and encourages a more integrated and participative engagement of learners.